Comparative analysis of different mulching materials on selected soil properties, growth, yield, and quality of moringa oleifera L. leaves - Sokombela, Asanda (My University, 2025)
Food insecurity in Africa is attributed from an underdeveloped agricultural sector heavily dependent on primary agriculture. Agricultural productivity faces diminishing soil fertility, resource constraints, environmental degradation, and insufficient investment in adding value to products and diversifying crops. To improve food insecurity, the production of high valued crops is a necessity. The cultivation of moringa trees in rural communities of South Africa emerges as one of many promising solutions to combat food insecurity and malnutrition, given its nutritional richness and versatility for both dietary enhancement and economic gain. Therefore, development of agronomic techniques that enhance food production is vital. Mulching has been identified as a strategy to reduce weeds and improve crop performance amongst rural smallholder farmers. Plastic mulching has been extensively used to boost the productivity of horticultural crops. Research has primarily concentrated on fruits and vegetables, overlooking other highly nutritious and economically valuable horticultural crops. A study was conducted to investigate the effects of different mulch materials on soil chemical properties, growth, yield, nutritional quality and metabolite composition of moringa leaves at the University of Fort Hare Research Farm, Alice, and was carried out as a randomized complete block design (RCDB) with six treatments replicated four times with a view to establishing a link between the different treatment and the seasonal variation. The treatment factors included (1) control (NM), (2) plant residues (OG), (3) red plastic mulch (PR), (4) black plastic mulch (PB), (5) green plastic mulch (PG), and (6) white plastic mulch (PW). The results indicated an interaction between treatment and season had no significant effect on the measured soil properties (p > 0.05). The treatments showed significant differences in sodium (p < 0.001) and potassium (p < 0.05), while season was significantly different in exchangeable acidity (p < 0.001), sodium (p < 0.001), potassium (p < 0.05), magnesium (p < 0.05), total carbon (p < 0.001), total nitrogen (p < 0.05) and phosphatase (p < 0.001). Black, white, and green plastic mulch exhibited the most significant increase in sodium and potassium compared to the other treatments. Seasonal effects showed that soil properties were higher in summer than autumn except for the phosphatase enzyme. Plant growth parameters were significantly improved in black plastic mulch compared to other mulch types used in the experiment. For instance, the black plastic mulch resulted in improvements in plant height, stem diameter, chlorophyll content, leaf width, leaf length, petiole width, petiole length, and yield (292 mm, 72 mm, 75.96 mm, 10.7 mm, 24 mm, 35 mm, and 1.84 kg/plot, respectively) compared to un-mulched plots. Mulching with black plastic significantly enhanced the nutrient composition of moringa leaves, attributed to improved growing conditions facilitated by plastic mulching. For example, the black plastic mulch maintained optimal moisture content (8.29), significantly enhanced proximate nutrients such as ash (14.93%), fat (4.92%), acid detergent fibre (29.87%), neutral detergent fibre (42.99 %), and crude protein (27.93 %) compared to un-mulched plots, and macro-nutrients, including phosphorus, nitrogen, calcium, magnesium, and potassium, were also improved. Conversely, sodium content was higher in red plastic mulch, while copper, manganese, iron, aluminum, and zinc were significantly higher in black plastic mulch. Amino acid analysis revealed that aspartic acid content (2.21%) was highest in black plastic mulch and lowest in red plastic mulch, whereas glutamic acid content (3.56%) was highest in the control and lowest in red plastic mulch. The results demonstrate the potential of plastic mulch technology as a beneficial agricultural practice for improving productivity and optimising nutrient profiles in moringa cultivation, thereby contributing to food security initiatives in African rural communities.
Thesis (Ph. D. ( Plant Production)) -- University of Limpopo, 2025
Keywords: Plastic mulch; Moringa; Smallholder farms; Food security; Climate change; Moringa oleifera; Mulching; Plant metabolites -- Biotechnology; Food security -- Climatic factor